THE CONCEPT OF «HOMELAND» IN LINGUISTIC, CULTUROLOGICAL AND PHILOSOPHICAL-AESTHETIC ASPECTS (Bulletin of Innovative Research, 2026)
This article is devoted to an interdisciplinary analysis of the concept of «Motherland» and the related categories of «Fatherland» within the context of the modern humanitarian paradigm. It examines the transition from a structural description of language to an anthropocentric and integrative approach, where linguistics closely interacts with cultural studies, psychology, and philosophy. The work explores the genesis of these concepts, from their etymological and lexical meanings to their consideration as philosophical categories, their hierarchy in the religious consciousness of early Christianity, and their role in shaping the national image of the world. Particular attention is paid to the value content of these concepts, their functioning as a «cultural code», and their significance for the national identity of new generations. The conclusions presented in three paragraphs are based on this work. The bibliography includes eleven sources.